IN DEFENCE OF PRIORITY REVIEW VOUCHERS - Sonderholm, Jorn (Bioethics, 2009)
Infectious and parasitic diseases cause enormous health problems in the developing world whereas they leave the developed one relatively unscathed. Research and development (R&D) of drugs for diseases that mainly affect people in developing countries is limited. The problem that relatively few drugs are available for diseases that cause an enormous burden of disease in the developing world is called the ‘availability problem’. In recent years, the availability problem has received quite a bit of attention. A number of proposals have been fielded as to how this problem might be minimized. Wild-card patent extensions, advance market commitments, cash prizes and the Health Impact Fund are prominent examples of such proposals. These proposals can be thought of as pull-mechanisms for R&D of drugs for neglected diseases. What has been coined a ‘priority review voucher’ is another pull-mechanism. This paper is a critical discussion of this pull-mechanism. First, the original priority review voucher scheme, as proposed by Ridley et al. (2006), is described. A number of objections to this scheme are thereafter presented. A few amendments to the original scheme are then suggested, and it is argued that with these amendments in place, the priority review voucher scheme constitutes an attractive way of stimulating R&D of drugs for neglected diseases.